2016
DOI: 10.1002/adem.201600297
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Low Weight Borides by Commercial Aluminum Alloys − A Basis for Metal Matrix Composite Fabrication

Abstract: Boron compounds are promising candidates for reinforcement of metals because of their high strength and stiffness at low specific weight. For composite fabrication the wetting behavior is important. Isothermal wetting of B 4 C, AlB 2 , CaB 6 , MgB 2 , and TiB 2 by liquid pure aluminum (99.5%) and the alloy AlSi10MgMn is studied at 700 C for 15 min in vacuum using the dispensed drop method. No wetting occurs during testing for all substrates. The contact angles remain constant for CaB 6 , MgB 2 , and TiB 2 , wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Even at 700 °C reactions take place and boron and aluminum rich phases (AlB 2 and Al 3 BC) are formed [11][12][13]. The wetting behavior of AlB 2 at 700 °C showed that aluminum melt infiltrated the AlB 2 substrate indicating good wettability [14]. No data on wetting properties of amorphous boron with liquid aluminum has been published so far, but aluminum can react with boron to AlB 2 at high temperatures promising reactive wetting [15].…”
Section: Introductionmentioning
confidence: 99%
“…Even at 700 °C reactions take place and boron and aluminum rich phases (AlB 2 and Al 3 BC) are formed [11][12][13]. The wetting behavior of AlB 2 at 700 °C showed that aluminum melt infiltrated the AlB 2 substrate indicating good wettability [14]. No data on wetting properties of amorphous boron with liquid aluminum has been published so far, but aluminum can react with boron to AlB 2 at high temperatures promising reactive wetting [15].…”
Section: Introductionmentioning
confidence: 99%